(untitled) - World Bank (Washington D.C., 2007)
This completely revised and updated second edition provides an accessible and straightforward overview of the World Bank Group's history, organization, mission, and purpose. Additionally, for those wishing to delve further into subjects of particular interest, the book guides readers to sources containing more detailed information, including annual reports, Web sites, publications, and e-mail addresses for various departments. It also provides information on how to work for or do business with the World Bank. A good introduction for anyone interested in understanding what the World Bank Group does and how it does it, this book shows readers who want to learn more where to begin.
Keywords: Economic assistance; Hỗ trợ kinh tế